2021
DOI: 10.1007/s11676-021-01390-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation in functional traits among wild cherry (Prunus avium L.) half-sib lines

Abstract: Understanding intra-specific variation in leaf functional traits is one of the key requirements for the evaluation of species adaptive capacity to ongoing climate change, as well as for designing long-term breeding and conservation strategies. Hence, data of 19 functional traits describing plant physiology, antioxidant properties, anatomy and morphology were determined on 1-year-old seedlings of wild cherry (Prunus avium L.) half-sib lines. The variability within and among half-sib lines, as well as the estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…In the long process of evolution and succession, plant species with widespread geographical distribution will respond adaptively to long-term changes in climate and geographical environment, thereby forming specific geographical provenances, which also reflects the long-term adaptation strategy of plants to the growing environment [1]. Thus, the ecological importance of intraspecific variation in functional traits of a species has gained increasing attention among researchers [2][3][4][5]. It has been shown that intraspecific trait variations can provide insights about trait responses to environmental variations and genetic improvement [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In the long process of evolution and succession, plant species with widespread geographical distribution will respond adaptively to long-term changes in climate and geographical environment, thereby forming specific geographical provenances, which also reflects the long-term adaptation strategy of plants to the growing environment [1]. Thus, the ecological importance of intraspecific variation in functional traits of a species has gained increasing attention among researchers [2][3][4][5]. It has been shown that intraspecific trait variations can provide insights about trait responses to environmental variations and genetic improvement [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its importance in fruit production, there is considerable interest in its wood by the furniture industry, but it also has a significant role in agroforestry (Russell 2003). Along with its economic role, it has ecological significance because the conservation of genetic variability of this species is considered to be an important part of the preservation of biodiversity, in general (Stojnić et al 2021). Therefore, many European countries have developed long-term breeding projects to improve the species' wood production and increase its tolerance to predominant biotic and abiotic stressors (Ducci et al 2013, Poljaković-Pajnik et al 2019.…”
Section: Introductionmentioning
confidence: 99%